Clinical characteristics and outcomes of cancer patients and their hospital course during the COVID-19 pandemic in a developing country. (February 2022) - Asghar, Muhammad Sohaib; Yasmin, Farah; Babar, Maryam Salma; Bin Zafar, Muhammad Daim; Ismail Shah, Syed Muhammad; Tahir, Muhammad Junaid
Abstract: In the new Coronavirus Disease 2019 (COVID-19) pandemic, cancer patients are considered a particularly susceptible population. We compared the type and magnitude of COVID-19 clinical manifestations among cancer patients in our center to non-cancer COVID-19 affected patients including 99 patients (28 cancer patients and 71 non-cancer patients). Hepatocellular carcinoma, breast carcinoma, and leukemia were the most common cancers. Diabetes and hypertension were prevalent comorbidities. Dyspnea, cough, fatigue, myalgia and diarrhea were statistically indifferent in both groups. Fatigue was more pronounced in cancer patients [OR: 2.573(1.025–6.460), p = 0.041] along with early onset of bilateral patchy consolidation [HR: 3.127(1.197–5.851), p = 0.032].